A preliminary screening study of pot marigold cultivars for resistance to powdery mildew - MOHD. AKRAM, S. IQBAL HUSAIN and (Indian Phytopathology, 2002)
Out of 27 commercial cultivars of marigold (Calendula offinalis) tested against Sphaerotheca fuliginea in microplot experiments, only Pacific beauty mixed was resistant.